The Concept of Information Asymmetry as a Theoretical Substantiation of the Phenomenon of Public Non-Financial Reporting - S. A. Samusenko (Учёт. Анализ. Аудит, 2018)
The global trend of widespread of public non-financial reporting makes the researchers face the task of finding its scientific basis. A unified theoretical and methodological basis of the concept of public non-financial reporting can be able to form the system of categories, laws, postulates and allow to implement effectively the processes of norm-setting, standardization and harmonization of public non-financial reporting with financial reporting. The purpose of the article is to provide the rationale for the choice of concept of information asymmetry as a fundamental theoretical basis to justify the phenomenon of public non-financial reporting. In the study the author applied the following research methods: analysis, synthesis, induction, deduction, comparison, generalization, and a systems approach. The article provides the results of analysis of extension of public non-financial reporting and identification of the problems of its application in Russian firms. The author systematizes the theoretical concepts be able to explain a phenomenon of public non-financial reporting: concept of sustainable development, the stakeholder theory, the doctrine of fair contracts. The author also demonstrates that the concept of information asymmetry is unifying for all of them and can be used to explain the voluntary adoption of obligations for additional disclosure of non-financial measurers by business. There is a need for a further scientific discussion of ideas about the implementation of public non-financial reporting as a prescriptive institutional or voluntary signaling mechanism, problem of its standardization, the counteract unfair usage of non-financial reporting to strengthen the negative effects of information asymmetry and the reallocation of market goods.